YTHDF2 interference suppresses the EMT of cervical cancer cells and enhances cisplatin chemosensitivity by regulating AXIN1. Issue 5 (30th April 2022) - Wu, Min; Chen, Guozhong; Liao, Xiaowen; Xiao, Lihua; Zheng, Jianqing
Abstract: M6A reader YTH structural domain family 2 (YTHDF2) has been recognized to play an oncogenic role in numerous tumors, but its role in cervical cancer has not been extensively discussed yet. This paper was designed to explore the role of YTHDF2 in cervical cancer and identify its underlying mechanism. The expression of YTHDF2 was first determined in cervical cancer cells by quantitative reverse‐transcription polymerase chain reaction and western blot. Then, the migration, invasion, and epithelial–mesenchymal transition (EMT) process were observed in YTHDF2‐knockdown Hela cells using wound healing, transwell and immunofluorescence assays. The cisplatin chemosensitivity of Hela cells was also investigated by assessing cell activity with cell counting kit‐8 and TUNEL (terminal deoxynucleotidyl transferase‐mediated dUTP nick end labeling). After MeRIP‐Seq assay and actinomycin D treatment to confirm the binding relationship between YTHDF2 and AXIN1, the migration, invasion, EMT process, and cisplatin chemosensitivity were assessed again in Hela cells silenced by YTHDF2 and AXIN1 or treated with Wnt agonist. YTHDF2 was increased in cervical cancer cells, and depletion of YTHDF2 led to reduced migration, invasion and EMT process but enhanced chemosensitivity of cisplatin in Hela cells. Furthermore, YTHDF2 could bind to and stabilize the expression of AXIN1. When the YTHDF2‐knockdown Hela cells were further transfected with AXIN1 knockdown or treated with Wnt agonist, the effects of YTHDF2 knockdown on the migration, invasion and EMT process were partially abolished, together with reduced cisplatin chemosensitivity. To sum up, we reported that YTHDF2 interference could suppress the EMT of cervical cancer cells and enhance cisplatin chemosensitivity by regulating AXIN1.